Czech.Math.J. 2017
DOI: 10.21136/cmj.2017.0540-15
|View full text |Cite
|
Sign up to set email alerts
|

A curvature identity on a~6-dimensional Riemannian manifold and its applications

Abstract: We derive a curvature identity that holds on any 6-dimensional Riemannian manifold, from the Chern-Gauss-Bonnet theorem for a 6-dimensional closed Riemannian manifold. We also introduce some applications of this curvature identity.2000 Mathematics Subject Classification. 53B20, 53C25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…In this paper, we provide the explicit formulae of Patterson's curvature identity that holds on 5-dimensional and 6-dimensional Einstein manifolds. We confirm that the curvature identities on the Einstein manifold from the previous work [8] are the same as the curvature identities deduced from Patterson's result. We also provide examples that support the theorems.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…In this paper, we provide the explicit formulae of Patterson's curvature identity that holds on 5-dimensional and 6-dimensional Einstein manifolds. We confirm that the curvature identities on the Einstein manifold from the previous work [8] are the same as the curvature identities deduced from Patterson's result. We also provide examples that support the theorems.…”
supporting
confidence: 90%
“…In [8], the authors consider the one-parameter deformation g(t) of g, using the fact that Euler characteristic is a topological invariant for the deformation, they got the universal curvature identity which holds on any 6-dimensional Riemannian manifold. In particular, they have the following.…”
Section: Curvature Identitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…But Damek and Ricci [3] found that there are many counterexamples if dimension n ≥ 7. Euh, Park and Sekigawa [4] provide a new proof of the Lichnerowicz conjecture for dimension n = 4, 5 in a slightly more general setting using universal curvature identities.…”
Section: Introductionmentioning
confidence: 99%